التخلص من الفوائد الربوية على والودائع والقروض المصرفية: دراسة فقهية تحليلية Getting Rid of Interests on Bank Deposits and Loans: A Juristic and Analytical Studyts on Bank Deposits and Loans: A Juristic and Analytical Study - Busari, Saheed (International Journal of Al-Turath In Islamic Wealth and Finance, 2021)
تعتبر الودائع والقروض من المنتجات المهمة للبنوك الإسلامية لأنها تلعب أدوارًا كبيرة في تعزيز الاقتصاد الإسلامي، على الرغم من نمو الاقتصاد الإسلامي، خاصة من مساهمات مؤسسته المالية، إلا أن العائدات الربوية تبدو مما يقطر ببال أصحاب القرار المصرفي لأن الشريعة الإسلامية الغراء لا تسمح بالتعامل مع الربا، لذلك أبرزت الدراسة كيفية التخلص من الربا على الودائع والقروض المصرفية وأحكامها الشرعية. وقد وظف الباحث المنهج الاستقرائي في جمع وترتيب المعلومات، والمنهج الوصفي في شرح المصطلحات الأساسية في البحث. لذلك يهدف هذا البحث إلى تسليط الضوء على واقع الفائدة الربوية في الودائع والقروض المصرفية، مع التركيز بشكل خاص على كيفية التخلص من الفائدة الربوية في البنوك. تظهر الدراسة ضرورة الأنشطة المالية الحديثة أنه لا يمكن لأحد الاستغناء عن المعاملات المالية المصرفية. ومع ذلك، فإن الأهمية الرئيسية للتخلص من الرصيد المحظور القائم على الفائدة هي منع الوسائل المحتملة لاستهلاك الربا أو التعامل مع الفائدة. Abstract Deposit and loan are important products for Islamic banks because they play important roles in promoting the Islamic economy. Despite the growth of the Islamic economy, especially from the contributions of its financial institution, the interest-based proceeds seem to be a concern to the banking decision-makers because the glorious Islamic Shariah does not permit dealing with the interest-based balance. Therefore, the study highlights how to get rid of the usury on bank deposits and loans and its shariah rulings. The study employed the inductive approach in gathering and arranging information. It also uses the descriptive method in explaining the basic terms in the research. This research aims to shed light on the reality of the usury balance in the bank deposits and loans, with a special focus on how to dispose of the usurious interest in banking. The necessity of the modern financial activities shows no one can dispense with the banking financial transaction. Moreover, the main significance of disposing the prohibited interest-based balance is blocking the potential means towards consumption of usury or dealing with interest. Keywords: Interest, Deposit, Loan, Bank.